Tantangan Guru Dalam Menghadapi Era Digital 5.0 (Studi pada SDN 5/81 Kampuno Kec. Barebbo Kab. Bone) - Kinas, Arni Anti; Nilawati, Fadiya (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2024)
ABSTRACT Teachers as educators have a major role in building the quality of education in Indonesia. The transformation of education towards digitalization has changed teachers' perspectives on teaching. Technology provides both opportunities and challenges for teachers. Therefore, teachers are required to continue learning, developing themselves and openly accepting developments in the era that are based on digital technology. This research uses qualitative research with a descriptive approach. This research was carried out in August 2024 at SDN 5/81 Kampuno. The subject criteria in this research are (1) Teachers at SDN 5/81 Kampuno (2) Have implemented the independent learning curriculum (3) Carry out technology-based teacher duties. Data and information were obtained through structured interviews, non-participant observation, and documentation, as well as searching for various literature in the form of books and research journals related to the object of study. Data is collected, reviewed and analyzed then carries out data reduction, data presentation, and draws conclusions. The research results show that the challenges faced by teachers in the 5.0 era include (1) the ability to master digital platforms from the Ministry of Education and Culture such as PMM (Merdeka Mengajar Platform); (2) Ability to design technology-based learning; (3) The ability to create a fun and interactive learning experience by choosing the right method and utilizing technology-based learning media; (4) The ability to measure student learning outcomes using digital evaluation tools such as the independent report card application. The efforts made by teachers to face challenges in the digital era 5.0 are (1) Learning independently through websites and YouTube channels; (2) Discuss with family, co-workers or superiors; (3) Participate in training programs organized by the District education office. Bone offline and online-based webinars initiated by the Ministry of Education and Culture.Â Keywords: Teacher Challenges, Digital Era